PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN KONTRAK CV. KIBAR SANDANG NUSANTARA - Meiliyana, Ratih Pratiwi; Lestari, Dian (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the influence of work discipline and work motivation simultaneously on the satisfaction of contract employees CV. Kibar Sandang Nusantara, to determine the influence of work discipline on the job satisfaction of contract employees CV. Kibar Sandang Nusantara, to determine the influence of work motivation on the satisfaction of contract employees CV. Kibar Sandang Nusantara. The population in this study is 32 contract employees. The sample taken was all contract employees. The method used in this study is descriptive with a quantitative approach using classical assumption tests, multiple regression and hypothesis tests. Data processing was carried out using SPSS version 26. The results of the study showed that work discipline and work motivation had an effect on the job satisfaction of contract employees CV. Kibar Sandang Nusantara. Then the results of further research show that work discipline has a positive and significant effect on the job satisfaction of contract employees CV. Kibar Sandang Nusantara. Furthermore, the results of data processing showed that work motivation had a positive effect on the job satisfaction of contract employees CV. Kibar Sandang Nusantara.